Bailouts and Systemic Insurance - Dell'Ariccia, Giovanni (IMF Working Papers; Working Paper ;, 2013)
We revisit the link between bailouts and bank risk taking. The expectation of government support to failing banks creates moral hazard-increases bank risk taking. However, when a bank's success depends on both its effort and the overall stability of the banking system, a government's commitment to shield banks from contagion may increase their incentives to invest prudently and so reduce bank risk taking. This systemic insurance effect will be relatively more important when bailout rents are low and the risk of contagion (upon a bank failure) is high. The optimal policy may then be not to try to avoid bailouts, but to make them 'effective': associated with lower rents.